Reaction mechanism of SiC-TiSi2 by melt infiltration method - ZHOU Yi-ran; LIU Hu; YANG Jin-hua; JIANG Zhuo-yu; LYU Xiao-xu; JIAO Jian (Cailiao gongcheng, 2019)
The melt infiltration method is one of the main preparation method of SiC matrix composites. Complex reactions and multi-component diffusion are involved in molten-Si infiltration of a C-based preform. In this study, SiC-TiSi2 was fabricated by Si melt infiltration and the TiSi2 was in-situ formed in the matrix of SiC. In order to explore the reaction mechanism of SiC-TiSi2, SEM, EDS and micro-beam XRD were determined to characterize the phase constitute and micro-structure in different regions along the Si melt infiltration direction. The results demonstrate that SiC, TiSi2 and Ti5Si3 which concentrate on the Si/SiC interface are found to be formed through the Si melt infiltration into the C-TiC preform. With the increase of temperature, the liquid phase of Ti-Si appears when exceeding the Si-TiSi2 eutectic temperature. And the liquid Ti-Si eutectic precipitates TiSi2 in the Si region during the cooling period of the sample. Moreover, the isolated SiC grain in Si region is produced by the precipitation from the dissolution of solid C in liquid Si.